2013
DOI: 10.2147/ijn.s38271
|View full text |Cite
|
Sign up to set email alerts
|

A phase I pharmacokinetic study of ursolic acid nanoliposomes in healthy volunteers and patients with advanced solid tumors

Abstract: Background: Ursolic acid is a promising anticancer agent. The current study aims to evaluate the single-and multiple-dose pharmacokinetics (PK) as well as the safety of ursolic acid nanoliposomes (UANL) in healthy volunteers and in patients with advanced solid tumors. Methods: Twenty-four healthy volunteers in the single-dose PK study were divided into three different groups, which received 37, 74, and 98 mg/m 2 of UANL. Eight patients in the multiple-dose PK study were administered with 74 mg/m 2 of UANL dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 22 publications
(23 reference statements)
1
16
0
Order By: Relevance
“…In order to investigate whether UA may improve cell susceptibility to DXR, the dose of UA in the combination experiments was adjusted to 10 μM for synovial sarcoma cells and 15 μM for leiomyosarcoma cells, because at these concentrations UA had a similar effect on cell viability and apoptosis in each of the respective cell lines according to their IC 50 values (Figs 1 and 2 ). A phase I pharmacokinetic study of UA nanoliposomes showed that plasma concentrations of this compound can reach up to 7.6 μM [ 27 ], which similar to the concentrations used here. The concentrations of DXR used in our study (0.1–10 μM) are typical for studies with doxorubicin-resistant or -insensitive cell lines and have been used by us [ 26 ] and others in similar in vitro studies performed with STS cell lines [ 28 , 29 ] as well as with other types of cancer cells [ 30 ] and can be clinically achieved in human plasma [ 31 ].…”
Section: Resultssupporting
confidence: 73%
“…In order to investigate whether UA may improve cell susceptibility to DXR, the dose of UA in the combination experiments was adjusted to 10 μM for synovial sarcoma cells and 15 μM for leiomyosarcoma cells, because at these concentrations UA had a similar effect on cell viability and apoptosis in each of the respective cell lines according to their IC 50 values (Figs 1 and 2 ). A phase I pharmacokinetic study of UA nanoliposomes showed that plasma concentrations of this compound can reach up to 7.6 μM [ 27 ], which similar to the concentrations used here. The concentrations of DXR used in our study (0.1–10 μM) are typical for studies with doxorubicin-resistant or -insensitive cell lines and have been used by us [ 26 ] and others in similar in vitro studies performed with STS cell lines [ 28 , 29 ] as well as with other types of cancer cells [ 30 ] and can be clinically achieved in human plasma [ 31 ].…”
Section: Resultssupporting
confidence: 73%
“…In addition, UA is reasonably tolerated in humans, and can achieve concentrations as high as 7.57 μM in the serum when supplied intravenously in nanoliposomes (49). We suggest use of UA in addition to approved P-gp inhibitors may be a valuable method to prevent or reverse tumor formation in P-gp-expressing human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Several phase I clinical trials have been conducted to evaluate the safety, tolerance and antitumor activity of intravenously administrated UAL. It was found that UAL was tolerable with manageable levels of toxicity, and could potentially improve remission rates in patients (Wang et al, 2013, 2015; Zhu et al, 2013; Qian et al, 2015). …”
Section: Introductionmentioning
confidence: 99%